Analisis Faktor yang Berhubungan dengan Medication Error Pasien Rawat Inap di Klinik X Kediri - Neni Probosiwi; Tsamrotul Ilmi; Nur Fahma Laili; Henni Wati; Lintang Bismantara B.G.PS; Anggeria Nimas Saputri; Desna Talia Saputri (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Medicaction error is an important problem in the health sector that can increase mortality, increase the duration of hospitalization, and increase the cost of treatment. Identifying the risk factors for medication errors is an important first step in preventing medication errors. This study aimed to identify the relationship between patient characteristics and medication errors in inpatients at clinic x. The study was conducted qualitatively with a cross-sectional design with recorded data. The study was conducted using clinical record data from July to December. The study sample consisted of 196 patients who met the inclusion criteria with a consecutive sampling technique. Analysis of the relationship between variables was carried out by chi-square analysis with a significance value of 5% (0.05). The results showed that inpatients at clinic x experienced medication errors of 17.86% which consisted of prescribing errors of 2.55% and administrative errors of 15.31%. Patient gender was not significantly associated with medication errors (p> 0.05). Patient age was significantly associated with medication errors (p<0.001). The number of drugs was significantly associated with medication errors (p<0.001). Length of stay was not significantly associated with medication errors (p < 0.05). Drug class was significantly related to medication error. The conclusion is that the patient's age, the number of drugs received by the patient and the class of drugs are factors related to the incidence of medication errors. The patient aspect also contributes to the risk factor for medication errors so that it can be considered in preventing medication errors in health practice by health workers.